Candidiasis and Oral Health - C N Roshin (Journal of Multidisciplinary Dental Research)
Candidiasis, primarily caused by Candida albicans, poses significant oral health concerns. This review highlights its clinical manifestations, diagnostics, and management strategies. Predisposing factors include poor oral hygiene and systemic conditions like HIV/AIDS and diabetes. Clinical presentation varies from asymptomatic colonization to symptomatic mucosal infections, with complications such as denture stomatitis. Diagnostics encompass clinical examination and various laboratory methods, guiding tailored treatment with topical or systemic antifungals. Prevention strategies targeting modifiable risk factors are crucial. Despite challenges like antifungal resistance, interdisciplinary collaboration among healthcare providers is essential for the effective management of oral candidiasis and its impact on overall health. Keywords: Candidiasis; Candida albicans; Oral health; Diagnostics; Antifungals; Prevention strategies